2015
DOI: 10.1002/dev.21325
|View full text |Cite
|
Sign up to set email alerts
|

Childhood social inequalities influences neural processes in young adult caregiving

Abstract: Childhood poverty is associated with harsh parenting with a risk of transmission to the next generation. This prospective study examined the relations between childhood poverty and non-parent adults’ neural responses to infant cry sounds. While no main effects of poverty were revealed in contrasts of infant cry vs. acoustically matched white noise, a gender by childhood poverty interaction emerged. In females, childhood poverty was associated with increased neural activations in the posterior insula, striatum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 79 publications
(96 reference statements)
3
39
1
1
Order By: Relevance
“…With regards to sex-specific effects of poverty, we reported that women with childhood poverty had a larger posterior insula response to infant cry than men with history of poverty [12]. There was no main effect of poverty or gender observed in this area, and the observed effect was an interaction of childhood poverty and sex.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…With regards to sex-specific effects of poverty, we reported that women with childhood poverty had a larger posterior insula response to infant cry than men with history of poverty [12]. There was no main effect of poverty or gender observed in this area, and the observed effect was an interaction of childhood poverty and sex.…”
Section: Introductionmentioning
confidence: 97%
“…One in four children in America are born to poverty [7], and identifying underlying mechanisms leading to long-term effects of poverty on physical and mental health is important in developing measures to prevent these adverse effects. There is accumulating evidence for anatomical and functional brain changes in adults as a result of childhood poverty, suggesting a neurobiological nature to the effects of childhood poverty [8,9,10,11,12,13]. Previous work has found this effect in brain regions involved in emotional response and emotion regulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-four adults from age 20 to 27 ( M = 23.72, SD = 1.31) participated in this study within the context of an ongoing, larger longitudinal study examining associations between income and child development (Kim et al 2015; Javanbakht et al 2015; Evans 2003; Kim et al 2013; Sripada et al 2014; Evans et al 2016; Liberzon et al 2015). Eleven of the 54 participants did not have data on at least one of our measurements of interest (e.g.…”
Section: Methodsmentioning
confidence: 99%